(3GdQSGdI GdOGeZI ddaGSb GdfLS GdaGVMI dCJHGYg Cgd GdQOI hGdHdSs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HGSe GdEdg GdMb hehdi GdNdb GdSdGe Ydi LeGYI GdGNhGf GdeMbbjf Cgd GdHUGFQ hGdjbjf s
(3BNQgG (B:s
(3hGdMeO def dGJMOg GdCdaGX hGdGacGQ hGdGSJeGY hGdTcQ ddehdi GdgGOi GdGeGe GdbGFe GdeWGY JeJ Hefg hdi GdGeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis